HUBUNGAN AKTIVITAS FISIK DENGAN VOLUME OXYGEN MAXIMAL (VO2MAX) PADA PEMAIN FUTSAL PUTRA DI SMAN 1 BOJONGGEDE - Bagas Prasetyo Aji; Kiki Rezki Faradillah; Agustiyawan; Rabia (Bajang Institute, 2026)
Background: Physical activity includes body movements using skeletal muscles that require stamina, such as daily tasks and sports. Based on MET, it is classified into light, moderate, and vigorous intensity, with low-intensity activity increasing the risk of chronic diseases. VO2Max is a key indicator of cardiovascular fitness that supports sports performance, including futsal. Objectives: This study examined the correlation between physical activity and VO2Max in male futsal players at SMAN 1 Bojonggede. Research Methods: This quantitative cross-sectional study was conducted at SMAN 1 Bojonggede (September–December 2024) with 22 selected players. Physical activity was measured using the GPAQ questionnaire, and VO2Max was assessed via the bleep test. Results: Results showed a correlation between physical activity and VO2Max of (p=0.032), although not necessarily linear. Other factors such as genetics, BMI, and weather also affect VO2Max, which is a limitation of this study. Conclusion: Male futsal players at SMAN 1 Bojonggede are 15-16 years old. Based on the distribution of physical activity, the majority of players fall into the moderate activity category, while the low physical activity category has the least number of respondents. In addition, the distribution of VO2Max showed that the majority of players had VO2Max levels